2011
DOI: 10.1302/0301-620x.93b9.26721
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of parallel and diverging screw angles in the stability of locked plate constructs

Abstract: We investigated the static and cyclical strength of parallel and angulated locking plate screws using rigid polyurethane foam (0.32 g/cm(3)) and bovine cancellous bone blocks. Custom-made stainless steel plates with two conically threaded screw holes with different angulations (parallel, 10° and 20° divergent) and 5 mm self-tapping locking screws underwent pull-out and cyclical pull and bending tests. The bovine cancellous blocks were only subjected to static pull-out testing. We also performed finite element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Along with an increasing angle, the screws converge more, and stability reduces. This effect for converging and diverging screws in an osteoporotic bone model has already been described …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Along with an increasing angle, the screws converge more, and stability reduces. This effect for converging and diverging screws in an osteoporotic bone model has already been described …”
Section: Discussionmentioning
confidence: 53%
“…This effect for converging and diverging screws in an osteoporotic bone model has already been described. 25,26 With a constant screw length of 45 mm the screw tip was likely to end in the middle of the vertebra for several specimens of larger dimensions. In clinical practice, for osteoporotic vertebra screws in a converging alignment, the longest ones possible are chosen.…”
Section: Discussionmentioning
confidence: 99%
“…8 Angulating locking screws may improve anchorage in bone, although in a biomechanical study, diverging screws may decrease construct stiffness in cyclical loading and static pull out testing. 20,22 The proximal screw of the distal plate segment is angulated to prevent intraosteotomy placement, but intraosteotomy screw placement was noted in two cases at 6 to 8 weeks' radiographic follow-up, potentially delaying bone union predisposing to implant failure. 20 No complica-tions were noted but osteotomy union scores of grades 1 and 2 were achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior lumbar interbody fusion surgery has been widely used to treat lumbar de generative disc disease [3][4][5][6]. However, patients with spinal decompression treatment using the ALP system still face compli cations such as implant loosening and breakage [7][8][9]. Many types of ALP systems with varied insertion angles of locking screws have been proposed to improve the biomechanical performances of the ALP systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with spinal decompression treatment using the ALP system still face compli cations such as implant loosening and breakage [7][8][9]. Past studies suggested that locking screws should be inserted with a particular inclined angle to strengthen the biomechanical performances of ALP systems [10], but oppo site conclusion has also been reached [9], Unfortunately, the screw orientations determined in past studies are mainly based on the surgeon's experience without biomechanical evidence. Past studies suggested that locking screws should be inserted with a particular inclined angle to strengthen the biomechanical performances of ALP systems [10], but oppo site conclusion has also been reached [9], Unfortunately, the screw orientations determined in past studies are mainly based on the surgeon's experience without biomechanical evidence.…”
Section: Introductionmentioning
confidence: 99%